Internationalization strategy and foreign distribution channels: analysis of the brazilian cosmetics company Natura - Silvia Novaes Zilbe; Carlos Henrique Mora Júnior; Francisco Lourenço da Silva (BBR: Brazilian Business Review)
This paper describes the internationalization process of the Brazilian company Natura Cosméticos S.A., whose competitive differential is the development of products based on the biodiversity of Brazilian flora. We specifically focus on the company's different choices of distribution channels in foreign markets. The study is exploratory, relying on content analysis of secondary data. The results indicate that the company's internationalization process has followed the model of the Uppsala school (learning) and that the company has maintained the same distribution strategy (direct sales) in markets with similar cultures (Latin America), but for the European market (Paris) it preferred to establish a physical store because of the cultural differences of that market. The change of the distribution channel model in the European market led the company to develop new organizational competencies.